Complex-phase fluorescent ceramic, wavelength conversion device and preparation method of wavelength conversion device
By using complex phase fluorescent ceramics in the wavelength conversion layer, the problems of low light extraction efficiency and insufficient mechanical properties of pure phase ceramics are solved, and the effects of efficient wavelength conversion and high central illuminance are achieved.
Patent Information
- Application Number
- CN202311340301.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
AI Technical Summary
The wavelength conversion layer of the existing reflective wavelength conversion device uses pure phase fluorescent ceramics, which leads to a large fluorescence divergence angle, low light extraction efficiency, and insufficient mechanical properties, which cannot meet the needs of various application environments.
Complex fluorescent ceramic particles and metal oxide particles with close melting points, close thermal expansion coefficient but different refractive index are prepared. The particles are evenly dispersed through the ball mill dispersion process, and complex fluorescent ceramics are prepared by SPS discharge plasma sintering process.
The light extraction efficiency and mechanical properties of complex phase ceramics are improved, the fluorescence scattering ability is enhanced, and the efficient wavelength conversion and high central illumination of the wavelength conversion device are realized, and the heat dissipation effect is good and the mechanical properties are excellent.
Smart Images

Figure BDA0004497054890000091 
Figure BDA0004497054890000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of wavelength conversion materials or devices, and more specifically, to a complex phase fluorescent ceramic, a wavelength conversion device and a preparation method thereof. Background Art
[0002] The wavelength conversion layer of existing reflective wavelength conversion devices mostly uses pure phase fluorescent ceramics. Pure phase fluorescent ceramics have advantages such as good thermal conductivity and heat resistance, strong blue light resistance, etc. However, since there is only fluorescent particle phase inside the ceramic and no scattering phase, the fluorescent device using pure phase ceramics as wavelength conversion material has a large fluorescence divergence angle and low light extraction efficiency. When used for laser lighting, there is a problem of low illumination at the center of the spot. Summary of the invention
[0003] The present invention aims to overcome at least one defect of the above-mentioned prior art and provides a complex phase fluorescent ceramic and a wavelength conversion device. The complex phase fluorescent ceramic has a strong scattering ability for fluorescence, a high light extraction efficiency, and good mechanical properties. The wavelength conversion device containing the complex phase fluorescent ceramic has a high wavelength conversion efficiency, a high central illumination of the emitted fluorescence, a good heat dissipation effect, and excellent mechanical properties.
[0004] Another object of the present invention is to provide a method for preparing the wavelength conversion device.
[0005] The technical solution adopted by the present invention is as follows:
[0006] A composite fluorescent ceramic comprises fluorescent ceramic particles and metal oxide particles, wherein the mass ratio of the fluorescent ceramic particles to the metal oxide particles is (0.25-4):1, and the difference in thermal expansion coefficient between the fluorescent ceramic particles and the metal oxide particles is less than 3.2*10 -6 / ℃, the difference in melting points between the fluorescent ceramic particles and the metal oxide is less than 415℃, the refractive indexes of the fluorescent ceramic particles and the metal oxide particles are different, the fluorescent ceramic particles include first fluorescent ceramic particles and second fluorescent ceramic particles, the D50 of the first fluorescent ceramic particles is 5-20μm, the D50 of the second fluorescent ceramic particles is 3-8μm, and the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is (2-10):1.
[0007] In one embodiment, the difference in refractive index between the fluorescent ceramic particles and the metal oxide particles is 0.1-0.4.
[0008] In one embodiment, the fluorescent ceramic particles and metal oxide particles are spherical particles or quasi-spherical particles.
[0009] In one embodiment, the particle size of the metal oxide particles is 50-500 nm.
[0010] In one embodiment, the fluorescent ceramic particles are YAG yellow fluorescent powder ceramic particles or LuAG green fluorescent powder ceramic particles; and / or the metal oxide particles are one or a mixture of aluminum oxide, magnesium oxide, yttrium oxide, yttrium aluminum garnet, and magnesium aluminum spinel.
[0011] In one embodiment, the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is (3-8):1.
[0012] The method for preparing the fluorescent ceramic comprises the following steps:
[0013] S1, weigh fluorescent ceramic particles and metal oxide particles in proportion, add an organic solvent, introduce them into a ball mill dispersing device, and perform ball milling dispersion for 6 to 12 hours to uniformly disperse the ceramic particle phase and the metal oxide particle phase to obtain a composite fluorescent slurry;
[0014] S2, drying the composite fluorescent slurry at 80±10°C for 8-24h to remove the organic solvent in the slurry, leaving the composite fluorescent ceramic powder; grinding the composite fluorescent ceramic powder into fine powder, and sieving it to obtain uniformly dispersed mixed fluorescent powder;
[0015] S3, introducing the mixed fluorescent powder into a mold, adopting an SPS spark plasma sintering process in which pressure and heating are performed simultaneously, setting the sintering temperature, loading pressure and sintering temperature, and obtaining a composite fluorescent ceramic.
[0016] The present technical solution also discloses a wavelength conversion device, comprising a fluorescent ceramic layer, a fluorescent reflective layer, a solder bonding layer and a heat dissipation substrate which are stacked in sequence, wherein the fluorescent ceramic layer is obtained by cutting and polishing the complex phase fluorescent ceramic, the thickness of the fluorescent ceramic layer is 80 to 200 μm, the thickness of the fluorescent reflective layer is 5-15 μm, the thickness of the solder layer is 10-40 μm, and the thickness of the heat dissipation substrate is 1-5 mm.
[0017] In one embodiment, the fluorescent reflective layer is a sintered silver reflective layer, which is formed by a composite of glass powder and silver powder, and the particle size of the silver powder is 0.3-5 μm; the glass powder is a Zn / B / Si / K / O system, and the softening temperature is 600-750°C.
[0018] The method for preparing the wavelength conversion device comprises the following steps:
[0019] (1) preparing a fluorescent ceramic layer: cutting the composite fluorescent ceramic into thin slices with a thickness of 100 to 400 μm, thinning and polishing, and preparing a fluorescent ceramic sheet with a thickness of 80 to 200 μm and a surface roughness Ra ≤ 0.5 μm;
[0020] (2) preparing a fluorescent reflective layer: adding silver powder and glass powder to a high boiling point solvent in proportion, grinding and dispersing, and preparing a silver paste; using a steel screen printing process, coating the silver paste on the polished surface of the fluorescent ceramic, controlling the paste viscosity, screen parameters and printing process, so that the thickness of the fluorescent reflective layer is 5 to 15 μm; placing the ceramic sheet covered with the fluorescent reflective layer in a high temperature oven at 120±10° C. for 20 to 60 minutes to remove most of the organic solvent in the fluorescent reflective layer, and then placing the pre-dried sheet in a high temperature sintering furnace at 750 to 900° C. for 10 to 60 minutes, so that the glass powder and the silver powder are sintered simultaneously, so that the fluorescent reflective layer is firmly bonded to the polished surface of the fluorescent ceramic;
[0021] (3) Solder packaging: Solder paste is printed on the sintered fluorescent reflective layer of the fluorescent ceramic layer and the surface of the heat dissipation substrate through a steel screen printing process, and the two sheets are bonded together. The printing process and screen parameters are controlled to ensure that the thickness of the solder layer is 10 to 40 μm. Subsequently, the vacuum reflow soldering technology is used to keep the above-mentioned bonded sheets at a temperature of 260-290°C for 20-60 seconds to solidify the solder. The fluorescent ceramic sheet covered with the fluorescent reflective layer is firmly bonded to the heat dissipation substrate to prepare the wavelength conversion device of this case.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: the present technical solution prepares the composite fluorescent ceramic by using fluorescent ceramic particles and metal oxide particles with similar melting points, similar thermal expansion coefficients, and different refractive indices, which can ensure that the composite ceramic structure is dense, the thermal expansion and contraction of different phases are consistent, and the scattering ability is strong; the present technical solution uses fluorescent powders with specific different coarse and fine particle sizes to improve the light extraction efficiency and mechanical properties of the ceramic for fluorescence. The wavelength conversion device containing the composite fluorescent ceramic has high wavelength conversion efficiency, high central illumination of the emitted fluorescence, good heat dissipation effect, and excellent mechanical properties. DETAILED DESCRIPTION
[0023] Most fluorescent ceramics on the market are pure-phase fluorescent ceramics. Although fluorescent ceramics have good thermal conductivity and heat resistance, and high blue light resistance, there is only a fluorescent particle phase inside the ceramics, and no scattering phase. As a result, fluorescent devices that use pure-phase ceramics as wavelength conversion materials have a large fluorescence divergence angle, low light extraction efficiency, and the central illumination of the emitted light still cannot meet the demand. In addition, the mechanical properties of existing fluorescent ceramics are also insufficient and cannot be well adapted to a variety of application environments.
[0024] Based on this, the present application proposes this technical solution.
[0025] A composite fluorescent ceramic comprises fluorescent ceramic particles and metal oxide particles, wherein the mass ratio of the fluorescent ceramic particles to the metal oxide particles is (0.25-4):1, and the difference in thermal expansion coefficient between the fluorescent ceramic particles and the metal oxide particles is less than 3.2*10 -6 / ℃, the difference in melting points between the fluorescent ceramic particles and the metal oxide is less than 415℃, the fluorescent ceramic particles and the metal oxide particles have different refractive indices, the fluorescent ceramic particles include first fluorescent ceramic particles and second fluorescent ceramic particles, the D50 of the first fluorescent ceramic particles is 10-20μm, the D50 of the second fluorescent ceramic particles is 3-8μm, and the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is (2-10):1.
[0026] The present invention provides a complex fluorescent ceramic system, in which metal oxide ceramic particles having a melting point close to that of fluorescent ceramic particles, a thermal expansion coefficient close to that of fluorescent ceramic particles, and a difference in refractive index are introduced into the interior of the fluorescent ceramic to prepare the complex fluorescent ceramic. Inside the complex fluorescent ceramic, the metal oxide particles serve as a matrix phase to form a network structure skeleton; the fluorescent ceramic particles serve as a filling phase and are filled into the skeleton structure formed by the metal oxide phase. The use of fluorescent ceramic particles and metal oxide particles with similar melting points can ensure that the complex materials of the two are sintered and densified at the same sintering temperature. The similar thermal expansion coefficient can ensure that the thermal expansion and contraction of the matrix phase and the filling phase in the complex ceramic are consistent during the cooling process after sintering, or when the complex fluorescent ceramic is used in a hot and cold shock cycle, so as to prevent the ceramic from cracking and damage. Due to the difference in refractive index between the metal oxide phase and the fluorescent ceramic phase, the scattering ability of the fluorescent ceramic to fluorescence is enhanced, so that the ceramic light extraction efficiency is increased, and the central illumination of the wavelength conversion device can be improved. In addition, in order to further enhance the fluorescence scattering ability of fluorescent ceramics, this case selects fluorescent particles with coarse and fine particles, so that fluorescent particles of different coarse and fine particles are evenly dispersed in the matrix phase formed by metal oxide ceramic particles. Among them, a certain proportion of coarse fluorescent particles can ensure the luminous efficiency of fluorescent ceramics, and the presence of fine fluorescent particles increases the crystallization nucleation points during the sintering process of metal oxides, hinders the growth of metal oxide grains, and then inhibits the growth of metal oxide particles, refines the grain size of the metal oxide phase, thereby increasing the number of grain boundaries of the metal oxide phase. The presence of a large number of grain boundaries enhances the scattering ability of fluorescent ceramics, thereby improving the light extraction efficiency of ceramics for fluorescence. In addition, the metal oxide phase after grain refinement and the dispersed fine fluorescent particles play a role in fine grain strengthening for the complex phase fluorescent ceramics, improve the strength and toughness of the fluorescent ceramics, and thus enhance the mechanical properties of the fluorescent ceramics.
[0027] Furthermore, the difference in refractive index between the fluorescent ceramic particles and the metal oxide particles is 0.1 to 0.4. The fluorescent ceramic particles and the metal oxide particles are spherical particles or quasi-spherical particles.
[0028] Further, the particle size of the metal oxide particles is 50-500 nm. More preferably, the median particle size D50 of the metal oxide particles is 80-200 nm.
[0029] Furthermore, the fluorescent ceramic particles are YAG yellow fluorescent powder ceramic particles or LuAG green fluorescent powder ceramic particles. The metal oxide particles are one of aluminum oxide, magnesium oxide, yttrium oxide, yttrium aluminum garnet, and magnesium aluminum spinel, or a mixture of several of them.
[0030] Preferably, the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is (3-8):1.
[0031] The preparation method of the composite fluorescent ceramic comprises the following steps:
[0032] S1. Weigh the fluorescent ceramic particles and metal oxide particles in proportion, add an organic solvent, introduce them into a ball mill dispersing device, and perform ball milling dispersion for 6 to 12 hours to uniformly disperse the ceramic particle phase and the metal oxide particle phase to obtain a composite fluorescent slurry. Through a suitable ball milling dispersion process, the coarse and fine fluorescent particles are uniformly dispersed in the matrix phase formed by the metal oxide ceramic particles. Specifically, the organic solvent can be anhydrous ethanol, isopropanol, ketone solvents, etc., preferably anhydrous ethanol.
[0033] S2. Dry the composite fluorescent slurry at 80±10° C. for 8 to 24 hours to remove the organic solvent in the slurry and leave the composite fluorescent ceramic powder; grind the composite fluorescent ceramic powder into fine powder and sieve it to obtain a uniformly dispersed mixed fluorescent powder.
[0034] S3, introducing the mixed fluorescent powder into a mold, adopting an SPS spark plasma sintering process in which pressure and heating are performed simultaneously, setting the sintering temperature, loading pressure and sintering temperature, and obtaining a composite fluorescent ceramic.
[0035] The technical solution also discloses a wavelength conversion device, comprising a fluorescent ceramic layer, a fluorescent reflection layer, a solder bonding layer and a heat dissipation substrate which are stacked in sequence. The fluorescent ceramic layer is obtained by cutting and polishing the complex phase fluorescent ceramic. The thickness of the fluorescent ceramic layer is 80-200 μm, the thickness of the fluorescent reflection layer is 5-15 μm, the thickness of the solder layer is 10-40 μm, and the thickness of the heat dissipation substrate is 1-5 mm. The fluorescent ceramic layer serves as a wavelength conversion layer, receives laser excitation, generates stimulated fluorescence, and achieves a wavelength conversion effect. The fluorescent reflection layer serves as a reflective structure layer, which better reflects the stimulated light back in the opposite direction of the excitation light. The heat dissipation substrate is used to quickly conduct the heat of the fluorescent ceramic layer to ensure the service life of the wavelength conversion device. The solder bonding layer is used to bond the fluorescent ceramic layer and the heat dissipation substrate together to achieve welding packaging.
[0036] Furthermore, the fluorescent reflection layer is a sintered silver reflection layer, which is formed by a composite of glass powder and silver powder, and the particle size of the silver powder is 0.3-5μm; the glass powder is a Zn / B / Si / K / O system, and the softening temperature is 600-750℃.
[0037] The method for preparing the wavelength conversion device comprises the following steps:
[0038] (1) Preparation of fluorescent ceramic layer: cutting the complex fluorescent ceramic into slices with a thickness of 100 to 400 μm, thinning and polishing, and obtaining fluorescent ceramic slices with a thickness of 80 to 200 μm and a surface roughness Ra ≤ 0.5 μm.
[0039] (2) Preparing a fluorescent reflective layer: adding silver powder and glass powder to a pine oil solvent in proportion, grinding and dispersing, and preparing a silver paste; using a steel screen printing process, coating the silver paste on the polished surface of the fluorescent ceramic, controlling the paste viscosity, screen parameters and printing process, so that the thickness of the fluorescent reflective layer is 5 to 15 μm; placing the above-mentioned ceramic sheet covered with the fluorescent reflective layer in a high-temperature oven at 120±10°C for 20 to 60 minutes to remove most of the organic solvent in the fluorescent reflective layer, and then placing the pre-dried sheet in a high-temperature sintering furnace at 750 to 900°C for 10 to 60 minutes, so that the glass powder and the silver powder are sintered simultaneously, so that the fluorescent reflective layer is firmly bonded to the polished surface of the fluorescent ceramic.
[0040] (3) Solder packaging: Solder paste is printed on the sintered fluorescent reflective layer of the fluorescent ceramic layer and the surface of the heat dissipation substrate through a steel screen printing process, and the two sheets are bonded together. The printing process and screen parameters are controlled to ensure that the thickness of the solder layer is 10 to 40 μm. Subsequently, the vacuum reflow soldering technology is used to keep the above-mentioned bonded sheets at a temperature of 260-290°C for 20-60 seconds to solidify the solder. The fluorescent ceramic sheet covered with the fluorescent reflective layer is firmly bonded to the heat dissipation substrate to prepare the wavelength conversion device of this case.
[0041] In order to allow those skilled in the art to better understand this solution, the solution is further described in detail below in conjunction with specific examples. The process methods used in the examples are all conventional methods unless otherwise specified; the materials used are all commercially available unless otherwise specified.
[0042] The performance parameters of the YAG yellow phosphor ceramic particles described in Examples 1 to 7 are as follows: Thermal expansion coefficient (6.9-7.3)*10 -6 / ℃; melting point: 1950℃; refractive index: 1.80-1.83; shape: spherical.
[0043] The performance parameters of the alumina particles described in Examples 1 to 6 are as follows: Thermal expansion coefficient (6.6-7.4)*10 -6 / ℃; melting point: 2054℃; refractive index: 1.68-1.73; median particle size D50: 80-200nm; shape: spherical.
[0044] The performance parameters of the magnesium-aluminum spinel particles described in Example 7 below are as follows: Thermal expansion coefficient (7.2-7.6)*10 -6 / ℃; melting point: 2250℃; refractive index: 1.95-2.05; median particle size D50: 80-200nm; shape: spherical.
[0045] The particle size of the silver powder described in the following Examples 8 to 15 is 0.3-5 μm.
[0046] The glass powder described in the following Examples 8 to 15 is a Zn / B / Si / K / O system glass powder with a softening temperature of 600-750°C.
[0047] The performance parameters of silicon oxide described in the following comparative example 2 are as follows: thermal expansion coefficient (0.4-0.8)*10 -6 / ℃; Melting point: 1400℃.
[0048] Unless otherwise specified, the raw materials used in the following examples are common commercially available products.
[0049] Example 1
[0050] A complex fluorescent ceramic comprises YAG yellow fluorescent powder ceramic particles and aluminum oxide particles, wherein the mass ratio of the YAG yellow fluorescent powder ceramic particles to the aluminum oxide particles is 1:1, and the fluorescent ceramic particles comprise first fluorescent ceramic particles and second fluorescent ceramic particles, wherein the D50 of the first fluorescent ceramic particles is 10 to 15 μm, the D50 of the second fluorescent ceramic particles is 3 to 5 μm, and the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is 3:1.
[0051] The preparation process is as follows:
[0052] S1. Weigh fluorescent ceramic particles and metal oxide particles in proportion, add anhydrous ethanol, introduce into a ball mill dispersing device, and perform ball milling dispersion for 6 to 12 hours to make the ceramic particle phase and the metal oxide particle phase evenly dispersed to obtain a composite fluorescent slurry.
[0053] S2. Dry the composite fluorescent slurry at 80±10°C for 8-24h to remove the organic solvent in the slurry and leave the composite fluorescent ceramic powder; introduce the composite fluorescent ceramic powder into a mortar and grind it manually so that the powder agglomerates are ground into fine powder, and then pass through a sieve to obtain a uniformly dispersed mixed fluorescent powder.
[0054] S3, introducing the mixed fluorescent powder into a graphite mold, adopting an SPS spark plasma sintering process in which pressure and heating are performed simultaneously, setting the sintering temperature, loading pressure and sintering temperature, and obtaining a composite fluorescent ceramic.
[0055] Example 2
[0056] A complex fluorescent ceramic comprises YAG yellow fluorescent powder ceramic particles and aluminum oxide particles, wherein the mass ratio of the YAG yellow fluorescent powder ceramic particles to the aluminum oxide particles is 1:1, and the fluorescent ceramic particles comprise first fluorescent ceramic particles and second fluorescent ceramic particles, wherein the D50 of the first fluorescent ceramic particles is 15 to 20 μm, the D50 of the second fluorescent ceramic particles is 5 to 8 μm, and the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is 3:1.
[0057] Example 3
[0058] A complex fluorescent ceramic comprises YAG yellow fluorescent powder ceramic particles and aluminum oxide particles, wherein the mass ratio of the YAG yellow fluorescent powder ceramic particles to the aluminum oxide particles is 0.25:1, and the fluorescent ceramic particles comprise first fluorescent ceramic particles and second fluorescent ceramic particles, wherein the D50 of the first fluorescent ceramic particles is 10 to 15 μm, the D50 of the second fluorescent ceramic particles is 3 to 5 μm, and the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is 3:1.
[0059] The preparation process is substantially the same as that of Example 1 and will not be described in detail here.
[0060] Example 4
[0061] A complex fluorescent ceramic comprises YAG yellow fluorescent powder ceramic particles and aluminum oxide particles, wherein the mass ratio of the YAG yellow fluorescent powder ceramic particles to the aluminum oxide particles is 4:1, and the fluorescent ceramic particles comprise first fluorescent ceramic particles and second fluorescent ceramic particles, wherein the D50 of the first fluorescent ceramic particles is 10 to 15 μm, the D50 of the second fluorescent ceramic particles is 3 to 5 μm, and the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is 3:1.
[0062] The preparation process is substantially the same as that of Example 1 and will not be described in detail here.
[0063] Example 5
[0064] A multiphase fluorescent ceramic comprises YAG yellow fluorescent powder ceramic particles and yttrium oxide particles, wherein the mass ratio of the YAG yellow fluorescent powder ceramic particles to the aluminum oxide particles is 1:1, and the fluorescent ceramic particles comprise first fluorescent ceramic particles and second fluorescent ceramic particles, wherein the D50 of the first fluorescent ceramic particles is 10 to 15 μm, the D50 of the second fluorescent ceramic particles is 3 to 5 μm, and the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is 2:1.
[0065] The preparation process is substantially the same as that of Example 1 and will not be described in detail here.
[0066] Example 6
[0067] A complex fluorescent ceramic comprises YAG yellow fluorescent powder ceramic particles and yttrium oxide particles, wherein the mass ratio of the YAG yellow fluorescent powder ceramic particles to the aluminum oxide particles is 1:1, and the fluorescent ceramic particles comprise first fluorescent ceramic particles and second fluorescent ceramic particles, wherein the D50 of the first fluorescent ceramic particles is 10 to 15 μm, the D50 of the second fluorescent ceramic particles is 3 to 5 μm, and the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is 10:1.
[0068] Example 7
[0069] A complex fluorescent ceramic comprises YAG yellow fluorescent powder ceramic particles and magnesium aluminum spinel particles, wherein the mass ratio of the YAG yellow fluorescent powder ceramic particles to the aluminum oxide particles is 1:1, and the fluorescent ceramic particles comprise first fluorescent ceramic particles and second fluorescent ceramic particles, wherein the D50 of the first fluorescent ceramic particles is 10 to 15 μm, the D50 of the second fluorescent ceramic particles is 3 to 5 μm, and the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is 10:1.
[0070] Embodiments 8 to 14
[0071] A wavelength conversion device comprises a fluorescent ceramic layer, a fluorescent reflective layer, a solder bonding layer and a heat dissipation substrate which are stacked in sequence, wherein the fluorescent ceramic layer is obtained by cutting and polishing the complex phase fluorescent ceramics described in Examples 1 to 7, respectively, the thickness of the fluorescent ceramic layer is 80 to 140 μm, the thickness of the fluorescent reflective layer is 5 to 10 μm, the thickness of the solder layer is 10 to 25 μm, and the thickness of the heat dissipation substrate is 1 to 3 mm.
[0072] The preparation process of the wavelength conversion device is as follows:
[0073] (1) Preparation of fluorescent ceramic layer: The composite fluorescent ceramic described in Example 1 is cut into thin slices with a thickness of about 300 μm, thinned and polished to a thickness of about 80 to 140 μm, and polished to obtain a fluorescent ceramic sheet with a surface roughness Ra ≤ 0.5 μm.
[0074] (2) Preparing a fluorescent reflective layer: adding silver powder and glass powder to a pine oil solvent in proportion, grinding and dispersing, and preparing a silver paste; using a steel screen printing process, coating the silver paste on the polished surface of the fluorescent ceramic, controlling the paste viscosity, screen parameters and printing process, so that the thickness of the fluorescent reflective layer is 5 to 10 μm; placing the above-mentioned ceramic sheet covered with the fluorescent reflective layer in a high-temperature oven at a temperature of 120±10°C and baking for 20 to 60 minutes to remove most of the organic solvent in the fluorescent reflective layer, and then placing the pre-dried sheet in a high-temperature sintering furnace at a high temperature of 750 to 900°C for 10 to 60 minutes, so that the glass powder and the silver powder are sintered simultaneously, so that the fluorescent reflective layer is firmly bonded to the polished surface of the fluorescent ceramic.
[0075] (3) Solder packaging: The tin-silver-copper solder paste is printed on the sintered fluorescent reflective layer of the fluorescent ceramic layer and the surface of the oxygen-free copper heat dissipation substrate with a thickness of 1-3 mm through a steel screen printing process. The two sheets are bonded together, and the printing process and screen parameters are controlled to make the solder layer thickness between 10 and 25 μm. Subsequently, the vacuum reflow soldering technology is used to keep the above-mentioned bonded sheets at a temperature of 260-290°C for 20-60 seconds to solidify the solder. The fluorescent ceramic sheet covered with the fluorescent reflective layer is firmly bonded to the heat dissipation substrate to prepare the wavelength conversion device of this case.
[0076] Embodiment 15
[0077] A wavelength conversion device comprises a fluorescent ceramic layer, a fluorescent reflective layer, a solder bonding layer and a heat dissipation substrate which are stacked in sequence, wherein the fluorescent ceramic layer is obtained by cutting and polishing the complex phase fluorescent ceramic described in Example 1, the thickness of the fluorescent ceramic layer is 140 to 200 μm, the thickness of the fluorescent reflective layer is 10 to 15 μm, the thickness of the solder layer is 25 to 40 μm, and the thickness of the heat dissipation substrate is 3 to 5 mm.
[0078] The preparation process is substantially the same as that of Examples 8 to 14 and will not be described again here.
[0079] Comparative Example 1
[0080] A complex phase fluorescent ceramic, whose structure and preparation process are substantially the same as those of Example 1, except that: the fluorescent ceramic particles used in this comparative example 1 are all YAG fluorescent ceramic particles with a size of 10 to 15 μm.
[0081] Comparative Example 2
[0082] A complex phase fluorescent ceramic, whose structure and preparation process are substantially the same as those of Example 1, except that: silicon oxide is used in place of aluminum oxide in Example 1 in this comparative example 2.
[0083] Comparative Example 3
[0084] A wavelength conversion device, whose structure and preparation process are substantially the same as those of Example 8, except that: the complex phase fluorescent ceramic described in Example 1 is used in this comparative example 3.
[0085] Comparative Example 4
[0086] A wavelength conversion device, whose structure and preparation process are substantially the same as those of Example 8, except that: this comparative example 4 adopts the complex phase fluorescent ceramic described in comparative example 2.
[0087] The wavelength conversion devices of the above Examples 8 to 15 and Comparative Examples 3 and 4 were installed in a laser light source system for performance testing. The laser light source system uses a blue laser light source with a maximum blue light output power of 80W and a laser spot size of Φ1.2mm. The test items include the following:
[0088] (1) Limit blue light power and limit luminous flux: The wavelength conversion devices of Examples 8 to 15 and Comparative Examples 3 and 4 are installed in the laser light source system. The power at which the luminous flux no longer increases or even decreases with the increase of blue light power is the limit value of the blue light power tolerance of the wavelength conversion device. The luminous flux measured at the limit blue light power is the limit luminous flux value of the wavelength conversion device.
[0089] (2) Central illuminance at 4W blue light power: The wavelength conversion devices of Examples 8 to 15 and Comparative Examples 3 and 4 were installed in the light source system. The central illuminance of the wavelength conversion devices of Examples 8 to 15 and Comparative Examples 3 and 4 was tested at a blue light power of 4W, a test distance of 10m and a 130mm imaging lens.
[0090] (3) High and low temperature cycle test: Test the change in the luminous flux of the wavelength conversion device before and after high and low temperature aging of the above-mentioned embodiments 8 to 15 and comparative examples 3 and 4. The luminous flux after aging drops to less than 90% of that before aging, which is the tolerable limit aging time. Calculate the number of cycles to evaluate its reliability. High and low temperature test environment: high temperature 85℃, low temperature -40℃. One cycle 2h.
[0091] (4) Bending strength: According to the national standard GB-T 4741-1999 ceramic bending strength test standard, the bending strength of the composite fluorescent ceramics of Examples 1 to 7, Comparative Example 1 and Comparative Example 2 was tested.
[0092] The test results are shown in Table 1.
[0093] Table 1
[0094] It can be seen from Examples 1 to 7 that the composite fluorescent ceramics prepared by the present invention have excellent flexural strength. It can be seen from the comparison between Example 1 and Comparative Example 1 that when fluorescent ceramic particles of a single particle size are used, the flexural strength of the composite fluorescent ceramics decreases significantly. The reason may be that the fluorescent ceramic particles with small particle sizes can play a role in fine grain strengthening for the composite fluorescent ceramics. It can be seen from the comparison between Example 1 and Comparative Example 2 that when the melting point difference between the metal oxide particles and the fluorescent ceramic particles is large, the flexural strength of the composite fluorescent ceramics decreases significantly. The reason may be that when the melting point difference between the metal oxide particles and the fluorescent ceramic particles is large, it is difficult to sinter and densify the two at the same temperature. In addition, the thermal expansion coefficient of silicon oxide is also very different from that of YAG. The sintering of the two particles as a composite ceramic can easily cause the ceramic to crack when used. It can be seen from Examples 8 to 15 that the wavelength conversion device described in the present invention has excellent aging resistance and wavelength conversion efficiency, and the central illumination of the emitted fluorescent light is high. By comparing Example 8 with Comparative Example 3, it can be seen that when fluorescent ceramic particles of a single particle size are used, the central illumination of the fluorescence emitted by the wavelength conversion device is low. The possible reason is that the presence of fine fluorescent particles increases the crystallization nucleation points during the sintering process of the metal oxide, hinders the growth of metal oxide grains, and then inhibits the growth of metal oxide grains, refines the grain size of the metal oxide phase, thereby increasing the number of grain boundaries of the metal oxide phase. The presence of a large number of grain boundaries enhances the scattering ability of the fluorescent ceramic, thereby improving the light extraction efficiency of the ceramic for fluorescence. By comparing Example 8 with Comparative Example 4, it can be seen that when the composite fluorescent ceramic is prepared with metal oxide particles and silicon oxide, the number of high and low temperature cycles of the prepared wavelength conversion device is significantly reduced, that is, the aging resistance of the wavelength conversion device is significantly reduced. The reason is that the composite fluorescent ceramic structure prepared with silicon oxide is not dense enough and is easy to crack. In addition, the wavelength conversion device's ultimate blue light power and ultimate luminous flux are also significantly reduced. The reason may be that silicon oxide has a worse thermal conductivity. When it is used as the matrix phase of a complex fluorescent ceramic, the thermal conductivity of the ceramic is low, resulting in poor blue light power resistance.
[0095] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A complex fluorescent ceramic, characterized in that: The invention comprises fluorescent ceramic particles and metal oxide particles, wherein the mass ratio of the fluorescent ceramic particles to the metal oxide particles is (0.25-4):1, and the difference in thermal expansion coefficient between the fluorescent ceramic particles and the metal oxide particles is less than 3.2*10 -6 / ℃, the difference in melting points between the fluorescent ceramic particles and the metal oxide particles is less than 415℃, the fluorescent ceramic particles and the metal oxide particles have different refractive indices, the fluorescent ceramic particles include first fluorescent ceramic particles and second fluorescent ceramic particles, the D50 of the first fluorescent ceramic particles is 10-20μm, the D50 of the second fluorescent ceramic particles is 3-8μm, and the mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is (2-10):
1.
2. The complex fluorescent ceramic according to claim 1, characterized in that: The difference in refractive index between the fluorescent ceramic particles and the metal oxide particles is 0.1 to 0.
4.
3. The complex fluorescent ceramic according to claim 1, characterized in that: The fluorescent ceramic particles and metal oxide particles are spherical particles or quasi-spherical particles.
4. The complex fluorescent ceramic according to claim 3, characterized in that: The particle size of the metal oxide particles is 50-500 nm.
5. The complex fluorescent ceramic according to claim 1, characterized in that: The fluorescent ceramic particles are YAG yellow fluorescent powder ceramic particles or LuAG green fluorescent powder ceramic particles; and / or the metal oxide particles are one or a mixture of aluminum oxide, yttrium oxide, and magnesium aluminum spinel.
6. The complex fluorescent ceramic according to claim 1, characterized in that: The mass ratio of the first fluorescent ceramic particles to the second fluorescent ceramic particles is (3-8):
1.
7. The method for preparing the composite fluorescent ceramic according to any one of claims 1 to 6, characterized in that: The steps include: S1, weigh fluorescent ceramic particles and metal oxide particles in proportion, add an organic solvent, introduce them into a ball mill dispersing device, and perform ball milling dispersion for 6 to 12 hours to uniformly disperse the ceramic particle phase and the metal oxide particle phase to obtain a composite fluorescent slurry; S2, drying the composite fluorescent slurry at 80±10°C for 8-24h to remove the organic solvent in the slurry, leaving the composite fluorescent ceramic powder; grinding the composite fluorescent ceramic powder into fine powder, and sieving it to obtain uniformly dispersed mixed fluorescent powder; S3, introducing the mixed fluorescent powder into a mold, adopting an SPS spark plasma sintering process in which pressure and heating are performed simultaneously, setting the sintering temperature, loading pressure and sintering temperature, and obtaining a composite fluorescent ceramic.
8. A wavelength conversion device, characterized in that: It comprises a fluorescent ceramic layer, a fluorescent reflective layer, a solder bonding layer and a heat dissipation substrate which are stacked in sequence, wherein the fluorescent ceramic layer is obtained by cutting and polishing the complex phase fluorescent ceramic according to any one of claims 1 to 7, the thickness of the fluorescent ceramic layer is 80 to 200 μm, the thickness of the fluorescent reflective layer is 5-15 μm, the thickness of the solder layer is 10-40 μm, and the thickness of the heat dissipation substrate is 1-5 mm.
9. The wavelength conversion device according to claim 8, characterized in that: The fluorescent reflection layer is a sintered silver reflection layer, which is formed by compounding glass powder and silver powder, wherein the particle size of the silver powder is 0.3-5 μm; the glass powder is a Zn / B / Si / K / O system, and the softening temperature is 600-750°C.
10. The preparation method according to claim 8 or 9, characterized in that: The steps include: (1) Preparing a fluorescent ceramic layer: cutting the composite fluorescent ceramic according to any one of claims 1 to 7 into thin slices with a thickness of 100 to 400 μm, thinning and polishing to obtain a fluorescent ceramic sheet with a thickness of 80 to 200 μm and a surface roughness Ra ≤ 0.5 μm; (2) preparing a fluorescent reflective layer: adding silver powder and glass powder to a high boiling point solvent in proportion, grinding and dispersing, and preparing a silver paste; The silver paste is coated on the polished surface of the fluorescent ceramic by using a steel screen printing process, and the viscosity of the paste, the screen parameters and the printing process are controlled so that the thickness of the fluorescent reflective layer is 5 to 15 μm; the ceramic sheet covered with the fluorescent reflective layer is placed in a high-temperature oven and baked at a temperature of 120±10° C. for 20 to 60 minutes to remove most of the organic solvent in the fluorescent reflective layer, and then the pre-dried sheet is placed in a high-temperature sintering furnace and sintered at a high temperature of 750 to 900° C. for 10 to 60 minutes, and the glass powder and the silver powder are sintered at the same time, so that the fluorescent reflective layer is firmly bonded to the polished surface of the fluorescent ceramic; (3) Solder packaging: Solder paste is printed on the sintered fluorescent reflective layer of the fluorescent ceramic layer and the surface of the heat dissipation substrate through a steel screen printing process, and the two sheets are bonded together. The printing process and screen parameters are controlled to ensure that the thickness of the solder layer is 10 to 40 μm. Subsequently, the vacuum reflow soldering technology is used to keep the above-mentioned bonded sheets at a temperature of 260-290°C for 20-60 seconds to solidify the solder. The fluorescent ceramic sheet covered with the fluorescent reflective layer is firmly bonded to the heat dissipation substrate to prepare the wavelength conversion device of this case.